A financeirização na correnteza alienada das águas do Canal do Sertão em Alagoas - Silva, Wanubya Maria Menezes da (2024)
This study focuses on Marx's theory of value and the uninterrupted process of expanded reproduction of capital in the contemporary phase of financialization, seeking to understand, through the channeling of the São Francisco river, with the Canal do Sertão venture, the monopolization of the territory by capital and the financialization of nature. The Canal do Sertão in Alagoas began to be executed in the context of debates on the climate crisis and the finiteness of energy resources; in this sense, it appears in CODEVASF reports as a proposal for sustainable development for the northeastern semi-arid region, confirming the recommendations of Agenda 21 for the use of water for the purpose of food production and sustainable rural development. For these reasons, we support the hypothesis that the transposition of the waters of the São Francisco River, via the Canal do Sertão, results from the multi-determinations of the productive restructuring of contemporary capital-imperialism, marked by the financialization of production and the expansion of global financial markets. From this perspective, the central objective of this work is to reflect on the expanded reproduction of capital in the Alagoas semi-arid region in its financialized phase, having as the fundamental object of this study the channeling of the São Francisco River in Alagoas. Starting from this principle, we argue that the globalized dynamics of financial capital, energized by the guidelines of the Washington Consensus, led Latin America to promote the private appropriation of the entire biodiversity of its territories, subverting the nature of the countries on the periphery of capitalism, from a common good to exchange value, a commodity. In this sense, we infer that the channeling process through which the São Francisco River passes, specifically through the Canal do Sertão venture, intensifies the monopolization of the sertanejo territory, integrating it into the globalized logic of interest-bearing capital. This reading is supported by official data and direct observation, which reveal the transposition channels as instruments for expanded reproduction, feeding back into global rent-seeking. The results obtained through research and interviews were instruments in understanding how the appropriation of the waters of the São Francisco river occurs, in order to debate the process of monopolization of labor and nature. In view of this process, this study aimed to construct a materialist and dialectical analysis on the production of space on the banks of the Canal do Sertão in Alagoas, from the perspective of understanding how it was idealized and planned within the logic of financialization of capital and water projects in the country in the last two decades, also evaluating which subjects actually participate in the management of the resource made available via the canal. The results found in the field allow us to articulate that the territories on the banks of the Canal are monopolized by financial capital, also presenting a tendency towards hydro-agribusiness.